Psychological Trauma among Health Care Professional during Covid-19 Pandemic - Asfa Anwar, Zehra Naqvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Covid-19 is a complex respiratory infectious disease that is impacting all sectors and industries. This pandemic is known to create a chaos among the healthcare sector and affecting psychological burden of healthcare professional. Less is known about the negative psychological influence of Covid-19 on the healthcare professionals, working in Pakistani hospitals. This study reported the prevalence of psychological trauma among healthcare professionals during Covid-19 pandemic. Material & Methods: The study adopted a cross-sectional study design and collected a quantitative sample of 195 healthcare professionals, who are working on front and second line. These professionals include; doctors, nurses, and other hospital staff. The data is collected from Liaquat National Hospital of Karachi, Pakistan during the period from April 2021 to March 2022. The study adopted a COPAQ questionnaire to assess psychological trauma among healthcare professionals. Results & Discussion:Majority of sample were aged less than or equal to 30-years, with more female healthcare professionals than male. Pearson Chi Square showed a significant association of psychological trauma with residence, socioeconomic status, working position and health care professionals with p<0.05. The odds ratio at confidence interval of 95%, for psychological trauma, in Univariate analysis urban resident were found 3.9 times, frontline workers gives 7.8 times, doctors gives 17.8 times and nurses gives 6.9 times more likely for psychological trauma and samples with income less than Rs. 25000 were found 0.13 times less likely for psychological trauma with p<0.05. In multivariate analysis none of the factors give significant association. Conclusion: The study recommended that a multi-sectoral and milti-pronged should be developed, to offer technical support for advancing of the healthcare system across the country. Future scholars are recommended to investigate the factors associated to psychological distress across different cities of Pakistan and make a comparison for better understanding. Keywords: Covid-19, Pakistan, Healthcare professionals, Frontline Healthcare Professionals, Psychological Distress